2002
DOI: 10.1111/j.1095-8649.2002.tb01747.x
|View full text |Cite
|
Sign up to set email alerts
|

The three‐spined stickleback as an environmental sentinel: effects of stressors on whole‐body physiological indices

Abstract: 15394-46914 2 Indicators of a generalised stress response (changes in cortisol, glucose, RNA:DNA ratio and total protein) when measured in whole-body preparations of individual sticklebacks display significant alterations in response to acute (hours) and chronic (days) disturbances and food withdrawal. In addition, changes in alkali-labile phosphorous, a specific biomarker of exposure to estrogenic contaminants, can be detected in whole-body preparations of estrogen-exposed sticklebacks confirming that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 101 publications
7
47
0
1
Order By: Relevance
“…Therefore, it could be suggested that absence of a difference in WB cortisol between control fish and those subjected to acute hypoxia was the result of fish entering 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 the experiment in a state of chronic stress. However, this seems unlikely as the WB cortisol levels of the fish in the current study were similar to those reported for the control fish (<8 ng/g) in a previous study (Pottinger et al, 2002) of the effect of various stressors on WB cortisol in three-spined sticklebacks. In this earlier study chronically stressed fish had WB cortisol levels of up to 50 ng/g after four days of crowding and confinement.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, it could be suggested that absence of a difference in WB cortisol between control fish and those subjected to acute hypoxia was the result of fish entering 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 the experiment in a state of chronic stress. However, this seems unlikely as the WB cortisol levels of the fish in the current study were similar to those reported for the control fish (<8 ng/g) in a previous study (Pottinger et al, 2002) of the effect of various stressors on WB cortisol in three-spined sticklebacks. In this earlier study chronically stressed fish had WB cortisol levels of up to 50 ng/g after four days of crowding and confinement.…”
Section: Discussionsupporting
confidence: 86%
“…Future studies should sample fish from a larger number of lentic and lotic stickleback populations and acquire more comprehensive water quality data with which to characterise the habitat of each population. Furthermore, although indices such as WB cortisol and glucose have been shown to be effective in measuring the acute and chronic stress response of a variety of small fishes, including sticklebacks (Reubush and Heath 1996;Scarabello et al 1992;King and Berlinsky 2006;Pottinger et al 2002) these are relatively crude measures of a complex biological response. Future investigations may benefit from a more refined approach to the assessment of HPI activity, including repeat measures in individual fish by the collection of water-borne cortisol and quantification of transcription factors such as hypoxia inducible factor-1, that are known to be associated with regulating the expression of physiologically relevant genes (Terova et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all fish, the condition factor (CF) was calculated according to Pottinger et al (2002), while somatic indexes for liver and gonad (HSI and GSI respectively) were calculated as (organ weight / fish weight).100.…”
Section: Metal Analysis In Watermentioning
confidence: 99%
“…This androgen-induced glue protein is synthetised by the kidney (Jakobsson et al, 1999). In environmental toxicology, stickleback is also considered as a valuable model species that enable the measurement of both biochemical and physiological responses to pollutants such as metals (Sanchez et al, 2005), pesticides (Katsiadaki et al, 2006;Sanchez et al, 2006;Wogram et al, 2001), halogenated organic compounds (Holm et al, 1994) and steroids (Pottinger et al, 2002;Sebire et al, 2007). Stickleback biomarker responses can also be used for the biomonitoring of freshwater ecosystem contamination as previously described for cholinesterase activities (Sturm et al, 2000) and liver histology (Handy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%